Methylmercury exposure induces ROS/Akt inactivation-triggered endoplasmic reticulum stress-regulated neuronal cell apoptosis. (1st September 2019) - Chung, Yao-Pang; Yen, Cheng-Chieh; Tang, Feng-Cheng; Lee, Kuan-I; Liu, Shing-Hwa; Wu, Chin-Ching; Hsieh, Shang-Shu; Su, Chin-Chuan; Kuo, Chun-Ying; Chen, Ya-Wen
Graphical abstract: Highlights: Methylmercury (MeHg) induced neuronal cell death underwent apoptosis. MeHg triggered endoplasmic reticulum stress-regulated neuronal cell apoptosis. ROS-mediated Akt inactivation signals involved in MeHg-induced neurotoxicity. Abstract: Epidemiological studies have positively linked mercury exposure and neurodegenerative diseases (ND). Methylmercury (MeHg), an organic form of mercury, is a ubiquitous and potent environmental neurotoxicant that easily crosses the blood-brain barrier and causes irreversible injury to the central nervous system (CNS). However, the molecular mechanisms underlying MeHg-induced neurotoxicity remain unclear. Here, the present study found that Neuro-2a cells underwent apoptosis in response to MeHg (1–5 μM), which was accompanied by increased phosphatidylserine (PS) exposure on the outer cellular membrane leaflets, caspase-3 activity, and the activation of caspase cascades and poly (ADP-ribose) polymerase (PARP). Exposure of Neuro-2a cells to MeHg also triggered endoplasmic reticulum (ER) stress, which was identified via several key molecules (including: glucose-regulated protein (GRP)78, GRP94, C/EBP homologous protein (CHOP) X-box binding protein(XBP)-1, protein kinase R-like ER kinase (PERK), eukaryotic initiation factor 2α (eIF2α), inositol-requiring enzyme(IRE)-1, activation transcription factor(AFT)4, and ATF6. Transfection with GRP78-, GRP94-, CHOP-, and XBP-1-specific small interfering (si)RNA significantly suppressed the expression of these proteins, and attenuated cytotoxicity and caspase-12, -7, and -3 activation in MeHg-exposed cells. Furthermore, MeHg dramatically decreased Akt phosphorylation, and the overexpression of activation of Akt1 (myr-Akt1) could significantly prevent MeHg-induced Akt inactivation, as well as apoptotic and ER stress-related signals. Pretreatment with the antioxidant N-acetylcysteine (NAC) effectively prevented MeHg-induced neuronal cell reactive oxygen species (ROS) generation, apoptotic and ER stress-related signals, and Akt inactivation. Collectively, these results indicate that MeHg exerts its cytotoxicity in neurons by inducing ROS-mediated Akt inactivation up-regulated ER stress, which induces apoptosis and ultimately leads to cell death.